Numeric Literacy Ability Of Elementary School Students Through Class AKM Activities at SDN Petukangan Selatan 05 - Widiansyah, Apriyanti; Fitriansyah, Fifit (Elementary Teacher Education Program, Majalengka University, 2025)
Assessment in learning should be the process of collecting and processing data to determine student learning outcomes. Learning assessment can be carried out using various techniques, such as exams, assignments, observations, and self-assessments. Minimum Competency Assessment is a basic competency assessment used to measure the development of students' self-capacity and positive participation in society. There are two essential competencies measured in the Minimum Competency Assessment, namely literacy and numeracy. However, in fact, after the Covid 19 pandemic, students' ability to understand texts and numbers has decreased, this is due to changes in learning patterns from face-to-face to online. For this reason, the purpose of this study is to see how the numeracy literacy skills of elementary school students are through the Minimum Competency Assessment activities in the class teaching campus program. The method used in this study is descriptive qualitative, namely by answering the actual conditions in the field carried out on grade 5 students of SDN Petukangan Selatan 05. The results of this study are that there are two literacy and numeracy programs, namely Fond of Literacy and Bilingual Class and Numeracy in Life and Numeracy Culture. With this program, it can be seen that students' numeracy literacy skills have increased by 23% literacy and 38% numeracy and this literacy and numeracy program helps students understand text and numbers in a broader and more enjoyable form than just knowing writing and numbers.